Bioenergetic Dysfunction and Inflammation in Alzheimer’s Disease: A Possible Connection - Wilkins, Heather M.; Carl, Steven M.; Greenlief, Alison C. S.; Festoff, Barry W.; Swerdlow, Russell H. (Frontiers in Aging Neuroscience, 2014)
Inflammation is observed in Alzheimer’s disease (AD) subject brains. Inflammation-relevant genes are increasingly implicated in AD genetic studies, and inflammatory cytokines to some extent even function as peripheral biomarkers. What underlies AD inflammation is unclear, but no “foreign” agent has been implicated. This suggests that internally produced damage-associated molecular pattern molecules (DAMPs) may drive inflammation in AD. A more complete characterization and understanding of AD-relevant DAMPs could advance our understanding of AD and suggest novel therapeutic strategies. In this review, we consider the possibility that mitochondria, intracellular organelles that resemble bacteria in many ways, trigger and maintain chronic inflammation in AD subjects. Data supporting the possible nexus between AD-associated bioenergetic dysfunction are discussed.